Avaliação dos microRNAs 29B e 142 e suas relações com as dnametiltransferases e as metaloproteinases na periodontite - Nayágara Moreira Dias da Silva (2018)
The pathogenesis of CP comprises complex interactions between periodontal pathogens and the immune response of the host. Factors involved in gene regulation may interfere with the predisposition of the beginning of disease signs and symptoms. In this aspect, are included the epigenetic mechanisms, which the DNA methylation and microRNA stand out. The objective of this work was to evaluate the transcription of microRNAs 142 and 29-b, and their relationships with DNA methyltransferases (DNMT) and metalloproteinases (MMP) -2 and 9 in CP. Gingival tissue biopsies were collected from healthy patients, as a control group, and with CP, with a total of 17 patients for each group. The samples were submitted to histological evaluation for sample characterization, extraction of Total RNA and conversion to cDNA and qPCR. We observed that the quantification of miRNAs 29b and 142-3p was higher in the CP compared to the control group. Higher levels of MMP-2 and lower levels of DNMT1 were observed in the CP group. Correlation analyzes in the CP group between the miRNAs evaluated and their possible targets showed a negative correlation between both miRNA142-3p and miRNA 29b with MMP2; as well as a positive correlation of 142-3p miRNA with DNMT1. Further studies are needed to evaluate the functional relevance of these findings.